Simulation, Human Factors and Defence Anaesthesia. Issue Volume 156:Issue (2010)Supplement 4 (1st December 2010) - Mercer, SJ; Whittle, C; Siggers, B; Frazer, RS
Abstract : Simulation in healthcare has come a long way since it's beginnings in the 1960s. Not only has the sophistication of simulator design increased, but the educational concepts of simulation have become much clearer. One particularly important area is that of non-technical skills (NTS) which has been developed from similar concepts in the aviation and nuclear industries. NTS models have been developed for anaesthetists and more recently for surgeons too. This has clear value for surgical team working and the recently developed Military Operational Surgical Training (MOST) course uses simulation and NTS to improve such team working. The scope for simulation in Defence medicine and anaesthesia does not stop here. Uses of simulation include pre-deployment training of hospital teams as well as Medical Emergency Response Team (MERT) and Critical Care Air Support Team (CCAST) staff. Future projects include developing Role 1 pre-deployment training. There is enormous scope for development in this important growth area of education and training.